LIFESTYLE, KNOWLEGE AND ATTITUDE ABOUT OBESITY AMONG OVERWEIGHT AND OBESE PERSONS - Jandric-Kocic, Marijana (HEALTH CARE, 2020)
Introduction/Aim: The aim of the study was to examine the impact of sociodemographic factors and body mass index on knowledge, attitude and perception of obesity in overweight and obese individuals.Methods: A cross-sectional study included 96 overweight and obese persons registered at the Health Center „Krupa on the Una River“ from October 1st, 2018 to October 1st, 2019. A general questionnaire and a questionnaire assessing knowledge, attitude and practice of obesity (KAP) were used in the study.Results: A cross-sectional study included 96 participants, that is, 66 (68.8%) overweight participants and 30 (31.3%) obese participants (obesity class I 29.2%, obesity class II 1%, obesity class III 1%). 52 (54.2%) men and 44 (45.8%) women participated in the study. The mean age of the study population was 56.0 ± 3.2 years. 5 (5.2%) research participants had university education, 61(63.5%) had some form of secondary education, while 30 (31.3%) completed only primary school. The study participants had no insight into the definition and meaning of body mass index, while knowledge of the basic principles of healthy eating and obesity therapy was low. Knowledge about the comorbidities of obesity proved to be satisfactory. Most of the respondents were aware of their obesity, felt that it could endanger their health and felt depressed because of their weight. The participants in the study had a sedentary lifestyle and unhealthy nutrition (excessive energy intake). The assessment of knowledge and perception of obesity was significantly (p
Keywords: Knowledge, perception, lifestyle, obesity, overweight